KEBERSIHAN DAN KESEHATAN PADA KEPADATAN TINGGI - Glenda Wongso; Joko Priyono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The world was shaken at the beginning of 2020 with the news of Covid-19 Virus. Indonesia is one of the countries affected by the impact, especially in Jakarta, that is still in a red zone area, which is one of the areas with the highest Covid-19 cases in Jakarta is West Pademangan in North Jakarta. West Pademangan is one of residential area with the highest population density, with a lot of slum settlements and limited public facilites to support that area. This design aims to reduce the density of buildings in order to create a distance of contact between communities in Pademangan. The presence of public facilities and green spaces also creates contact distance between communities in addition to reducing the level of density. This study used a qualitative descriptive approach, with primary data in the form of survey results and field studies as well as secondary data obtained from government data, research journals, and books. The data collection technique uses the comparative method, the overlay method, and the analysis method using the Solid-Void concept and Organic Architecture. The concept of health and hygiene in the building is inspired by a concept of a medical mask which consists of 3 layers but still can "breathe" consisting of breath brick layer and TiO2 layer. In addition, a space for interaction between communities is also created on the ground floor of the flats which is used as a public area consisting of a garden, canteen, gym, market and retail shop as a place for buying and selling transactions. Keywords: dwelling; health; high density; hygiene  AbstrakDunia diguncang pada awal tahun 2020 dengan berita Virus Covid-19.  Indonesia menjadi salah satunya negara yang terkena dampaknya, terutama di Jakarta yang sampai saat ini masih menjadi kawasan zona merah, dimana salah satunya adalah kawasan Pademangan Barat di Jakarta Utara yang merupakan salah satu kawasan dengan kasus Covid-19 tertinggi di Jakarta. Pademangan Barat merupakan kawasan permukiman dengan kepadatan penduduk yang tinggi, kumuh dan fasilitas umum yang terbatas untuk menunjang kawasan tersebut. Rancangan ini bertujuan untuk mengurangi kepadatan bangunan agar tercipta adanya jarak kontak antarmasyarakat di Pademangan. Kehadiran fasilitas umum dan ruang hijau turut serta menciptakan jarak kontak antar masyarakat di samping menurunkan tingkat kepadatan. Penelitian ini menggunakan pendekatan deskriptif kualitatif, dengan jenis data primer berupa hasil survey dan studi lapangan juga data sekunder yang diperoleh dari data pemerintah, jurnal penelitian, dan buku. Teknik pengumpulan data menggunakan metode komparasi, metode penampalan, dan metode analisis dengan menggunakan konsep Solid-Void dan Arsitektur Organik. Konsep hidup bersih dan sehat tercipta pada bangunan dengan konsep yang terilhami dari masker yang terdiri dari 3 lapisan tetapi masih bisa “bernafas” yang terdiri dari breath brick dan lapisan TiO2. Selain itu, ruang interaksi antar masyarakat juga tercipta pada lantai dasar rumah susun yang dijadikan sebagai area publik yang terdiri dari taman, kantin, gym, market, dan retail shop sebagai tempat transaksi jual-beli.